2012
DOI: 10.1177/009885881203800208
|View full text |Cite
|
Sign up to set email alerts
|

What is the Meaning of Health? Constitutional Implications of Defining “Medical Necessity” and “Essential Health Benefits” under the Affordable Care Act

Abstract: When the government decides to assume a major role in providing and paying for healthcare, the government also has to decide exactly what constitutes appropriate, reasonable, or essential healthcare under its program. Congress, of course, recognized this necessity when it passed the Patient Protection and Affordable Care Act (ACA), and the statute itself provides authority to the Secretary of Health and Human Services (HHS) to determine the “essential health benefits” that must be covered under the ACA beginni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…There is evidence that gun control achieved through background checks reduces homicide and suicide. [68][69][70][71][72] Previous studies reported success in reducing the burden of gun deaths through policy changes in Brazil and other countries. 71 Indeed, enforcing gun control policies has proven effective in reducing mortality in a variety of contexts.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that gun control achieved through background checks reduces homicide and suicide. [68][69][70][71][72] Previous studies reported success in reducing the burden of gun deaths through policy changes in Brazil and other countries. 71 Indeed, enforcing gun control policies has proven effective in reducing mortality in a variety of contexts.…”
Section: Discussionmentioning
confidence: 99%
“…The IOM report also emphasized that the ACA ensures that people who are denied care have a right to appeal the decision, and it acknowledged that many definitions of medical necessity currently exist but refused to select a single definition to apply to all ACA marketplace plans. Instead, according to Hill (2012), the report "embraced the view that '[t]he central question is whether the treatment is medical in nature and whether the individual can be expected to medically benefit from it'" (pp. 450-451).…”
Section: Medical Necessitymentioning
confidence: 99%
“…The tension identified here -between viewing reproductive health services as fundamentally private health care decisions and viewing them as primarily political or moral issues subject to public debateis not new, nor is it unique to the CPC and abortion counseling cases. 81 For example, in the Supreme Court oral argument in McCullen v. Coakley, dealing with the constitutionality of a buffer zone surrounding an abortion clinic, attorneys for the clinic referred to the anti-abortion activists as "protestors," whereas attorneys challenging the buffer zone called them "counselors." 82 Indeed, Justice Scalia highlighted the discrepancy in terminology when he stated: This is not a protest case.…”
Section: A Dispute About Speech or A Dispute About Health Care?mentioning
confidence: 99%